A decreasing trend in zinc deficiency in Mexican children aged 1-4: analysis of three national health and nutrition surveys in 1999, 2006 and 2018-19 - Vanessa De la Cruz-Góngora; Teresa Shamah-Levy; Salvador Villalpando; Ignacio Méndez-Gómez Humarán; Rosario Rebollar-Campos; Juan Rivera-Dommarco (Instituto Nacional de Salud Pública, 2021)
Objective. To describe trends in zinc deficiency (ZD) prevalence among preschool-age Mexican children, and explore differences in this trend among beneficiaries of the conditional cash transfer program Progresa/Oportunidades/ Prospera (CCT-POP). Materials and methods. The serum zinc information of children aged 1-4 who participated in the ENN 1999, Ensanut 2006 and Ensanut 2018-19 was analyzed. ZD was categorized according to IZiNCG cutoff values. Logistic regression models were used to identify personal participant characteristics associated with ZD trends, and tests for interactions between survey CCT-POP beneficiaries were applied. Results. ZD decreased by 22.3 percentage points (pp) between ENN 1999 and Ensanut 2018-19; among CCT-POP beneficiaries, the decrease was 58.6 pp. Overweight was associated with higher odds of ZD (OR=2.18, p=0.023). Conclusions. In the last 19 years, ZD declined significantly among preschool-age Mexican children. Child beneficiaries of the social program CCT-POP showed the largest reduction of ZD.